Implementation Of an E-Commerce Website Based on A Content Management System at Vape.Bill Store Indonesia - Pratama, Muhammad Rafi; Hin, Lauw Li (Universitas Budi Luhur, 2024)
In the rapidly advancing digital era, the implementation of information technology has become a key element in enhancing business competitiveness, including in the vape industry. This research focuses on the development and implementation of an e-commerce website based on a Content Management System (CMS) for Vape.Bill Store, with the aim of improving operational efficiency, stock management, and consumer accessibility. The main issues faced by Vape.Bill Store include limited promotion, inefficient stock management, and difficulty in reaching customers outside its local area. The methodology used in this study involves system analysis using Fishbone Diagram and Business Model Canvas (BMC) to identify the root causes of the problems, as well as the development and design of a CMS-based system using the Unified Modeling Language (UML) approach for functional modeling. The results of the research show that the implementation of CMS allows for easier management of products, promotions, and transactions, while also expanding market reach and increasing sales. CMS has proven to be an effective solution for small and medium-sized businesses to build e-commerce platforms that are adaptive to technological developments and business needs